Giant Cutaneous Horn Arising in an Epidermal Nevus. Issue 5 (7th August 2017) - Cardis, Michael A.; Kirkorian, Anna Yasmine
Abstract: Cutaneous horns, which rarely occur in children, can overlie a large array of pathologic lesions that range from benign to malignant. When a cutaneous horn is encountered, it is not the horn itself that is of relevance, it is the nature of the underlying disease that dictates overall prognosis and management. In this report we present a case of a cutaneous horn arising within a linear verrucous epidermal nevus and briefly review cutaneous horns, with an emphasis on their clinical implications and differential diagnosis.